High-dose statins for the prevention of recurrent ischemic stroke: a systematic review and meta-analysis of randomized controlled trials - Muhammed Siddique Shahid; Mariam Safwan Bourgleh; Adel Alharfi; Shahad Albariqi; Lamia Albalawi; Rema Alohali; Turki Albaqami; Moaz Safwan Bourgleh (Annals of Saudi Medicine)
INTRODUCTION: Ischemic stroke (IS) is a leading cause of disability and mortality, with fatal outcomes increased with recurrent strokes. This systematic review and meta-analysis of randomized controlled trials (RCTs) evaluated the safety and efficacy of high-dose statins for secondary IS prevention. METHODS: This review was regestered on PROSPERO (registration number: CRD42024574088). Cochrane methodology was followed in this review and comprehensively searched PubMed, Embase, Cochrane Library and clinicaltrial.gov, to include all RCTs conducted from 2004 to 2024, comparing high-dose statins (simvastatin ≥40 mg, atorvastatin ≥40 mg, and rosuvastatin ≥20 mg) with low-dose statins, placebo, or standard care. Outcomes of this review were recurrent IS reduction and adverse events reported in RCTs. RESULTS: Nine RCTs involving 5,503 patients, with male patients ranging from 25.8% to 81.6% were included. Compared to controls, high-dose statins did not significantly reduce risks for secondary IS (OR 0.78, 95% CI [0.61, 1.00], P=.05) and hemorrhagic stroke (OR 0.85, 95% CI [0.56, 1.29], P=.45). Furthermore, no differences were observed in mortality rates and adverse events between groups. CONCLUSION: Treatment with high dose statins didn't reduce the risk of stroke recurrence or improve mortality, though further research is needed.